2010
DOI: 10.1089/gtmb.2009.0024
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Mitochondrial tRNA Gene Mutations and Their Association with Specific Clinical Phenotypes in Patients with Type 2 Diabetes Mellitus of Coimbatore

Abstract: The association of mitochondrial DNA mutation with type 2 diabetes mellitus (T2DM) is well established. In this study we aimed to assess the frequency of A3243G, A8296G, and other mitochondrial mutations with reference to clinical features in the diabetic population of Coimbatore, India. The study group included 150 patients (89 women and 61 men) with T2DM, whereas the control group included 100 nondiabetic people (59 women and 41 men). Genotyping was done by polymerase chain reaction followed by single-strand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Earlier reports showed the association of mitochondrial DNA mutations like 1310C < T, 1382A < C, 1438G < A, 1201A < G, 3243A < G, 3252A < G, 3256A < T, 3264A < C, 3271A < C, 3290T < C, 3303C < T, 3316G < A, 3394T < C, 8296A < G, 8344A < G, 11778G < A, 12026A < G, 12258C < A, 14577T < C, 14709T < C and 16189T < C [ 16 20 ] with T2D development. Particularly, mutation in tRNA Leu gene at 3243 (A < G) position and in the subunits of NADH dehydrogenase 1 and 4 have been reported to have strong association with incidence of diabetes in different populations [ 18 , 19 , 21 , 22 ]. There was a significant correlation between the number of somatic mtDNA ATP6 mutations and the smoking and consuming betel-nut with paan (OR: 3.52; 95 % CI: 0.96–12.11) for the type 2 diabetes along with drinking alcohol (OR: 4.62; 95 % CI: 1.82–14.53).…”
Section: Discussionmentioning
confidence: 99%
“…Earlier reports showed the association of mitochondrial DNA mutations like 1310C < T, 1382A < C, 1438G < A, 1201A < G, 3243A < G, 3252A < G, 3256A < T, 3264A < C, 3271A < C, 3290T < C, 3303C < T, 3316G < A, 3394T < C, 8296A < G, 8344A < G, 11778G < A, 12026A < G, 12258C < A, 14577T < C, 14709T < C and 16189T < C [ 16 20 ] with T2D development. Particularly, mutation in tRNA Leu gene at 3243 (A < G) position and in the subunits of NADH dehydrogenase 1 and 4 have been reported to have strong association with incidence of diabetes in different populations [ 18 , 19 , 21 , 22 ]. There was a significant correlation between the number of somatic mtDNA ATP6 mutations and the smoking and consuming betel-nut with paan (OR: 3.52; 95 % CI: 0.96–12.11) for the type 2 diabetes along with drinking alcohol (OR: 4.62; 95 % CI: 1.82–14.53).…”
Section: Discussionmentioning
confidence: 99%
“…Duraisamy et al, 2010 performed a mitochondrial study of the A3243G variant in South Indian T2DM patients. The variant was identified in two patients with similar clinical characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…The variant was identified in two patients with similar clinical characteristics. They concluded that these mitochondrial mutations indicate a genetic predisposition to DM in the Coimbatore South Indian population (Duraisamy et al, 2010). In our study, we found eleven mutations in the GDM cases and three in the non-GDM subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondria play an imperative role in glucose metabolism, insulin secretion and biogenesis, hence its dysfunction is reportedly found to play a crucial role in diabetes development (Gerbitz et al 1996;Choo Kang et al 2002). Earlier reports showed the association of mitochondrial DNA mutations like 1310C [T, 1382A[C, 1438G[A, 1201A[G, 3243A[G, 3252A[G, 3256A[T, 3264A[C, 3271A[C, 3290T[C, 3303C[T, 3316G[A, 3394T[C, 8296A[G, 8344A[G, 11778G[A, 12026A[G, 12258C[A, 14577T[C, 14709T[C and 16189T[C (Giles et al 1980Alcolado et al 1994;Kalinin et al 1995;Seneca et al 1998;Chinnery et al 2000;Hattori et al 2003;Pranoto 2005;Brandon et al 2005;Liu et al 2007;Mezghani et al 2010;Vijaya Padma et al 2010;Duraisamy et al 2010;Weng et al, 2013) with T2D development. Particularly, mutation in tRNA Leu gene at 3243 (A[G) position and in the subunits of NADH dehydrogenase 1 and 4 have been reported to have strong association with diabetes incidence in different populations (Kalinin et al 1995;Zhao and Zhang 2001;Lam et al 2001;Pranoto 2005;Yu et al 2004;Duraisamy et al 2010;Vijaya Padma et al 2010).…”
Section: Discussionmentioning
confidence: 99%